Maintenance Preventive Scheduling of Critical Components in Offset Printing Machine (Case Study : PT. XYZ) - L. Patiapon, Marcy (UNIPA PRESS, 2021)
Maintenance activities are generally considered as supporting activities in the production process. However, this activity is very important because it contributes directly to the smooth running of the production process and productivity. PT. XYZ is a company engaged in mass media or newspapers since September 8, 2015. In the newspaper production process, PT. XYZ experienced delays in the production process due to damage to the component parts of the printing machine, in which the Offset printing machine is the core printing machine that is always used to print newspapers. Based on data on the frequency of damage during 2020 which was obtained from observations and interviews with operators, damage to machine components for 1 year on the offset printing machine counted 73 times that it was damaged. Thus making the machine stop operating from the effective working time of the machine, which is 264 days/year. This is due to the unavailability of a machine maintenance schedule because the company is still implementing a breakdown maintenance system. Thus the researcher aims to calculate the value of the identified critical components and calculate the effective time of machine operation for scheduling replacement of critical components of offset printing machines using the Reliability Centered Maintenance method. Based on the results of data processing using the Reliability Centered Maintenance method, the contactor component is determined as a critical component where the value of the Risk Priority Number is 72 with an average checking time of 11,250 minutes and component replacement time of 7 times/year. For this reason, it can be concluded that the contactor is a critical component with a damage value of 72 and the scheduling time for component replacement is 7 times in 1 year.